2014
DOI: 10.5714/cl.2014.15.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microporosity on nitrogen-doped microporous carbons for electrode of supercapacitor

Abstract: Nitrogen-doped microporous carbons were prepared using a polyvinylidene fluoride/ melamine mixture. The electrochemical performance of the nitrogen-doped microporous carbons after being subjected to different carbonization conditions was investigated. The nitrogen to carbon ratio and specific surface area decreased with an increase in the carbonization temperature. However, the maximum specific capacitance of 208 F/g was obtained at a carbonization temperature of 800°C because it produced the highest microporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Nevertheless, they argued that biomass char has potential as a DCFC fuel because the porous characteristics of biomass char and the functional groups on the char surface promote the electrochemical reactions in the low current density region. A c c e p t e d M a n u s c r i p t studies reported biochar as an electrode in supercapacitors [156,157]. Those studies reported that the capacitive performance of biochar electrode was influenced by surface functional groups, electric conductivity, and pore structure and distribution as well as the specific surface area [158].…”
Section: Other Applicationsmentioning
confidence: 98%
“…Nevertheless, they argued that biomass char has potential as a DCFC fuel because the porous characteristics of biomass char and the functional groups on the char surface promote the electrochemical reactions in the low current density region. A c c e p t e d M a n u s c r i p t studies reported biochar as an electrode in supercapacitors [156,157]. Those studies reported that the capacitive performance of biochar electrode was influenced by surface functional groups, electric conductivity, and pore structure and distribution as well as the specific surface area [158].…”
Section: Other Applicationsmentioning
confidence: 98%
“…Many researchers have studied the use of carbonaceous materials for gas adsorption. Carbonaceous materials have been widely used in industrial applications such as adsorbents [29][30][31], supercapacitors [32], and batteries. They can be produced from natural materials, including wood, charcoal, petroleum coke, sawdust, and coconut shell.…”
Section: Effect Of Surface Treatment On Carbonaceous Materials For Gamentioning
confidence: 99%
“…Thus, high porosity is an important feature of carbon adsorbents. Porous carbons can be prepared by a number of techniques, such as direct carbonization of various precursors and templating other porous materials such as metal-organic frameworks (MOFs) and zeolites [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high porosity is an important feature of carbon adsorbents. Porous carbons can be prepared by a number of techniques, such as direct carbonization of various precursors and templating other porous materials such as metal-organic frameworks (MOFs) and zeolites [20][21][22][23].Sucrose is a disaccharide comprising a-glucose and b-fructose.Sucrose can be obtained from sugar cane or sugar beet and can be used as a precursor for preparation of porous carbon. Cai et al reported the sucrose-based template carbon materials and their hydrogen storage capacity (1.43 wt.%, 700 8C) [24].…”
mentioning
confidence: 99%